Differential Regulatory Role of Pituitary Adenylate Cyclase–Activating Polypeptide in the Serum‐Transfer Arthritis Model. Issue 10 (October 2014) - Botz, Bálint; Bölcskei, Kata; Kereskai, László; Kovács, Miklós; Németh, Tamás; Szigeti, Krisztián; Horváth, Ildikó; Máthé, Domokos; Kovács, Noémi; Hashimoto, Hitoshi; Reglődi, Dóra; Szolcsányi, János; et al.
<x xml:space="preserve">Abstract</x> Objective Pituitary adenylate cyclase–activating polypeptide (PACAP) expressed in capsaicin‐sensitive sensory neurons and immune cells has divergent functions in inflammatory and pain processes. This study was undertaken to investigate the involvement of PACAP in a mouse model of rheumatoid arthritis. Methods Arthritis was induced in PACAP−/− and wild‐type (PACAP+/+) mice by K/BxN serum transfer. General features of the disease were investigated by semiquantitative scoring, plethysmometry, and histopathologic analysis. Mechano‐ and thermonociceptive thresholds and motor functions were also evaluated. Metabolic activity was assessed by positron emission tomography. Bone morphology was measured by in vivo micro–computed tomography, myeloperoxidase activity and superoxide production by bioluminescence imaging with luminol and lucigenin, respectively, and vascular permeability by fluorescent indocyanine green dye study. Results PACAP+/+ mice developed notable joint swelling, reduced grasping ability, and mechanical (but not thermal) hyperalgesia after K/BxN serum transfer. In PACAP−/− mice clinical scores and edema were significantly reduced, and mechanical hyperalgesia and motor impairment were absent, throughout the 2‐week period of observation. Metabolic activity and superoxide production increased in the tibiotarsal joints of wild‐type mice but were significantly lower in PACAP−/− animals. Myeloperoxidase activity in the ankle joints of PACAP−/− mice was significantly reduced in the early phase of arthritis, but increased in the late phase. Synovial hyperplasia was also significantly increased, and progressive bone spur formation was observed in PACAP‐deficient mice only. Conclusion In PACAP‐deficient mice with serum‐transfer arthritis, joint swelling, vascular leakage, hyperalgesia, and early inflammatory cell accumulation are reduced; in the later phase of the disease, immune cell function and bone neoformation are increased. Elucidation of the underlying pathways of PACAP activity may open promising new avenues for development of therapy in inflammatory arthritis.